Geographical distribution map of Alternaria blight of rapeseed-mustard in India: Geographical distribution map of Alternaria blight of rapeseed-mustard in India - P D MEENA,; PK RAI,; PANKAJ SHARMA, (Journal of Oilseeds Research, 2023)
Alternaria blight (AB) disease caused by Alternaria brassicae (Berk.) Sacc., and A. brassicicola (Schwein) Wiltshire is a most common destructive disease which causes upto 35% yield loss through disturbing the photosynthetic activities in plant. During 2004 to 2020, AB severity data revealed that the disease severity decreased by 7% in rapeseed-mustard growing area. Prevalence of AB severity observed in Uttarakhand (48.5%), Himachal Pradesh (47.1%), Punjab (43.7%), Bihar (38.9%), Assam (38.7%), Jharkhand (38.7%), Uttar Pradesh (38.0%), Jammu & Kashmir (31.7%), Haryana (28.5%), Madhya Pradesh (25.3%), Chhatishgarh (24.1%), and Rajasthan (15.5%). However, AB severity was negligible in Gujarat, Maharashtra and Tamil Nadu states due to unfavourable weather conditions. Although, AB severity trend was fluctuating between 18.4 to 45.2%, but severity on Rohini and Varuna at Bharatpur was observed below 15% since last 10 years which was higher upto 25% severity recorded during 2003 to 2006. AB severity was recorded maximum on Brassica rapa ssp. Toria (39.3%) followed by, B. rapa ssp. Yellow Sarson (34.9%), B. juncea (31.1%) and Eruca sativa (30.9%). Although, B. napus (26.0%) and B. carinata (22.1) were least affected crops species with AB which could be used for developing tolerance/resistance in B. juncea through traditional breeding methods.